Diversity of Hard Ticks (Acari, Ixodidae) Infestion in Arabian Camel in Iraq - Hadi, Afkar M.; Makawi, Zainab A. (Iraqi Journal of Science, 2024)
A total of 1346 hard ticks (863♂ and 483 ♀) infested 104 camels, 60 alive camels with 93.33% infestation rate and 44 carcasses of camels had 79.54% infestation rate The total infestation rate was 87.5 %.The current study results revealed ten species of hard ticks family Ixodidae Koch, 1844 related to genus Hyalomma as following: H. dromedarii Koch, 1844, H. schulzii Morel, 1969, H. turanicum Pomerantsev, 1946, H. excavatum Koch, 1844, H. truncatum Koch, 1844, H. scupense Schulzii, 1919, H. marginatum Koch, 1844, H. anatolicum Koch, 1844, H. rufipes Koch, 1844, H. impeltatum Schulze & Schlottke, 1930 from camel Camelus dromedarius Linnaeus, 1758 collected from 21 regions belonging to six provinces in middle, west and south of Iraq where camels were bred in abundance. According to the current results, camels are considered a new host for three species of genus Hyalomma: H. truncatum, H. marginatum rufipes. These results may be of more importance as being the available data for risk topic about camels infested with hard ticks.